FORMATION OF THE NEW WORLD VIEW, NEW PERSON, NEW SOCIETY OF THE FUTURE - Valentina A. Voronkova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Objective: To substantiate the anthropological approaches to the definition of the noosphere and cosmic consciousness and the world, a new consciousness, a new man, a new society of the future, by which humankind can go to a new state of mutual responsibility. Society should be based on a spiritual basis, a person must develop in harmony with the universe, so the philosophers need to change the philosophy of survival of the globalized world in the development of philosophy and spirituality, which is a new matrix of the discourse of development and outlook of the universe. The meaning of the individual in society - to be useful to society and to the person, to be a master, to live in harmony with people and nature. Methodology. Study is based on the methd of hermeneutical analysis.The scientific novelty of this work is shown in the results, which indicate the formation of the noosphere worldview that seeks to realize the idea of V.Vernadsky, which manifests itself in the context of a harmonious relationship of scientific knowledge, philosophy, and religion, which produce a variety of forms of dialogue between people of different cultural backgrounds, nationalities, religions, generations and gender. Conclusions. The new philosophy of development in the twenty-first century, aimed at forming a new society, a new consciousness, a new person should be directed to: a) the confrontation process of self-destruction of the human person and the destructive tendencies of the environment, and b) the creation of conditions for the harmonization of public self-regulatory systems: organization, person, environment, society, and c) the creation of conditions for the realization of the creative potential of every person (regardless of its level of consciousness) to identify the direction of development of the creative work, and d) the formation and implementation of creative management at all levels.